Macrophages Derived From Human Induced Pluripotent Stem Cells Are Low-Activated “Naïve-Like” Cells Capable of Restricting Mycobacteria Growth - Nenasheva, Tatiana; Gerasimova, Tatiana; Serdyuk, Yana; Grigor'eva, Elena; Kosmiadi, George; Nikolaev, Alexander; Dashinimaev, Erdem; Lyadova, Irina (Frontiers in Immunology, 2020)
In peripheral tissues, immune protection critically depends on the activity of tissue resident macrophages, which makes our understanding of the biology of these cells of great significance. Until recently, human macrophage studies were largely based on the analysis of monocyte-derived macrophages that differ from tissue resident macrophages by many characteristics. To model tissue resident macrophages, methods of generating macrophages from pluripotent stem cells have been developed. However, the immunological properties of macrophages derived from pluripotent stem cells remain under-investigated. In this study, we aimed to perform the multifarious immunological characteristics of macrophages generated from human induced pluripotent stem cells (iMs), including an analysis of their phenotype, secretory and antibacterial activities, as well as their comparison with macrophages derived from blood monocytes and infected lung tissue. We report that iMs displayed the morphology and the CD11b+CD45+CD14+ phenotype typical for mononuclear phagocytes. The cells co-expressed markers known to be associated with classically (CD80, CD86, CCR5) and alternatively (CD163 and CD206) activated macrophages, with a bias towards a higher expression of the latter. iMs secreted pro-inflammatory (IL-6, CXCL8, CCL2, CCL4, CXCL1, CXCL10) and anti-inflammatory (IL-10, IL-1RA, CCL22) cytokines with a high IL-10/IL-12p70 index (>20). iMs were phagocytic and restricted Mycobacterium tuberculosis growth in vitro by >75%. iMs differed from blood monocytes/macrophages by a lower expression level of HLA-DR and the CD14+16dim phenotype and shared several phenotypic characteristics with lung macrophages. In response to LPS, iMs up-regulated HLA-DR and produced TNF-α. IFN- increased iM reactivity to LPS, but did not increase iM mycobactericidal capacity. The results characterize iMs as differentiated but low-activated/low-polarized ‘naïve-like’ macrophages that are capable of mounting inflammatory and antibacterial responses when exposed to inflammatory stimuli or pathogens. iMs represent a valuable model for studying antibacterial responses of tissue resident macrophages and for developing approaches to modulating macrophage activity.